Intentionality : past and future - Forrai, Gábor, 1962-; Kampis, György, 1958- (Value inquiry book series ;, 2005)
This book contains eleven original papers about intentionality. Some explore current problems such as the status of intentional content, the intentionality of perception and emotion, the connections between intentionality and normativity, the relationship between intentionality and consciousness, the characteristics of the intentional idiom. Others discuss the work of historical figures like Locke, Brentano, Husserl and Frege.